Menelusuri Pola Fiqh Muhammadiyah Dalam Perspektif Tarikh Tasyri' - Hadi Hidayaturrahman (Bayani, 2021)
The discourse that is always discussed from time to time is how the concept and position of madzhab in Islam. The beginning of the emergence of schools of thought has appeared since thousands of years ago. In the Tasyri Date, the madzhab tradition is a scientific tradition that has long been in effect after the Prophet Saw and generations of companions died. In Indonesia, it is undeniable that in general various sects have grown and developed, especially in matters of fiqh, both worship and muamalah. This is inseparable from the fact that the majority of Muslims claim to be Islamic schools of thought. Muhammadiyah as an Islamic missionary movement, amar ma'ruf nahi munkar, has since the beginning affirmed itself as an organization based on the al-Qur'an and as-Sunnah and does not tie itself to any particular Madzhab. If this statement is not read correctly and proportionally there is an impression that Muhammadiyah is truly anti-Madzhab. This paper intends to give one view that Muhammadiyah is not what they say. Through the method of reading or the perspective of the Tasyri Date with various sources, be it books, books, journals or other sources, various Fiqh patterns that developed during the Prophet's period, the Sahaba period, the Imam Mujtahid period, the Taqlid period and the period of Ijtihad reopening will be found. So that from these periods it will be found how the Muhammadiyah fiqh pattern and its position towards the opinion of the Madzhab.